The wolf gift [compact disc, unabridged] - Rice, Anne, 1941- (Random House Audio, 2012)
A young man is bitten in the darkness by a creature he cannot see, setting into motion his transformation into a beast that is neither man nor wolf. As the desire to embrace his new form becomes too great to resist, he finds himself still wanting to perform good, even while in his most savage state. On a search to find out more about his new "gift," he finds something even more unexpected: love.